Exploring Possibilities of Tourism in Pokhara - Kunwar, Prakash (A Bi-annual South Asian Journal of Research & Innovation, 2024)
A collection of activities that people do when temporarily removed from their normal surroundings is referred to as tourism. Regarding foreign exchange, income and employment generation, and development activities like infrastructure and human resource development, it has significant potential for both developed and developing countries. The study's methodology is a descriptive qualitative examination of various primary and secondary data based on studies of various publications. As a result of the study, opportunities have been identified, including the potential for two million tourists the creation of public private partnership models, the potential for disaster resilience, the potential for significant tourism development, the decentralization of Nepalese tourism, and investment opportunities. Comparably, the study's findings include inadequate national carriers, low connection, inadequate investments, inadequate  infrastructures, poor agency cooperation, scarce resources, and marketing.